Tecnología y género : la inmersión del ser humano en las video-esculturas de Ana Claudia Múnera (1995-2000) (2017)
"The historiographical void that currently exists regarding the work of colombian videoartist Ana Claudia Múnera (Medellín, 1966) is shocking, since during the '90s it was celebrated and situated alongside the work of famous artists such as Fernando Arias, María Fernanda Cardoso, Doris Salcedo and Elias Heim... This thesis seeks to reinstate Munera's artwork back into colombian art history, examining the role of technology in her video-sculptures. To that end, based on the theoretical framework of cyberfeminism, laid out by philosophers such as Donna Haraway and Sadie Plant, I propose a new reading of three of her most representative artworks, "Máquina" (1996), "Vestido de novia" (1997), and "Matriz" (1998), implying that these pieces do not necessarily pay tribute to the "female roles", but actually call this very notion into question." -- Tomado del Formato de Documento de Grado.